Поняття та особливості правової охорони лісів - Мендик, Л.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Исследованы основные подходы к пониманию общих понятий «правовая охрана» и «правовая защита», на основе которых автором обоснованно понятие «правовая охрана лесов». Автор доказывает, что правовая охрана лесов - это совокупность правовых норм и правоотношений, которая связана с рациональным использованием, воссозданием, повышением производительности и защитой лесов. In this article investigational basic going near understanding of general concepts «legal safeguard» and «legal defence», on the basis of which by an author grounded family concept «legal safeguard of the forests». In opinion of author, a legal safeguard of the forests is a body corporate and politic of laws and legal relationships, which is related to the rational use, recreation, increase of the productivity and defence of the forests with a purpose maintenances and increases ecological, aesthetically beautiful, educate and other their properties.